Does Postmodernism Undermine Politics? - Murphy, John W. (Sociologija. Mintis ir veiksmas, 2015)
Postmodernism represents an assault on the approach realists have taken to conceptualizing knowledge and order. It shows no regard for the principles and standards that have allowed societies to grow and prosper. With respect to current politics, it is believed that postmodernism discards the commitments and moral guidelines that have enabled a range of activists to intervene at appropriate times to improve the conditions of disadvantaged persons. It seems that postmodernism has undermined any valid basis for formulating a fair and equitable social contract and giving credence to postmodernism is synonymous with embracing social atomism and accepting the laissez-faire outlook on economics and other aspects of social life. Because the philosophy of laissez-faire provides no basis for order other than freely chosen contacts, which many conservatives believe are optional, social correctives have no purpose. Indeed, considering the resulting elusive nature of society, where are interventions supposed to be directed?